Progressive Extracellular Matrix Disorganization in Chemically Induced Murine Oral Squamous Cell Carcinoma. (29th August 2012) - Fuentes, B.; Duaso, J.; Droguett, D.; Castillo, C.; Donoso, W.; Rivera, C.; Venegas, B.; Kemmerling, U.
Abstract : Introduction . Oral squamous cell carcinoma (OSCC) is one of the ten most common cancers affecting the human population. Tumor pathogenesis implies a multistep process in which cells acquire features that enable them to become tumorigenic and ultimately malignant. The process of OSCC carcinogenesis can be reproduced in animal models, the OSCC induction with 4-nitroquinoline-1-oxide (4NQO) in mice is a widely used tool for studying tumor pathogenesis. Objective . The aim of the present study was to determine the progressive changes in basal lamina and connective tissue remodeling during 4NQO-induced OSCC carcinogenesis. Material and Methods . Samples were classified according to "International Histological Classification of tumors" in mild, moderate, and severe dysplasia and invasive carcinoma. Five samples of each pathologic entity and control healthy tongues were used. Immunohistochemical analysis of collagen IV as well as histochemical analysis of glycosylated molecules (PAS) and collagen I (Picro Sirius red) were performed. Results . During experimental-induced carcinogenesis by 4NQO a progressive basal lamina destruction and collagen I disorganization in adjacent connective tissue can be observed. Conclusion . Our results confirm previous studies that show alterations in extracellular matrix (ECM) in malignant lesions, validating the experimental carcinogenesis induced by 4NQO.